SKRINING KESEHATAN PRIMER DAN FAKTOR RISIKO HIPERTENSI PADA PESERTA JKN DI SEMARANG - Sary, Annisa Novita; Hasrinal, Hasrinal; Dasril, Oktariyani; Rosa, Audrey Faiza; Marsyah, Finy (Ensiklopedia of Journal, 2025)
Abstract: Hypertension is a very serious health problem and non-communicable disease (NCD). The World Health Organization (WHO) report in 2023 estimates the prevalence of hypertension at 22% of the total population. Based on the results of the BPJS Health primary health history screening, 14% of participants had a potential risk of hypertension. In the city of Semarang, hypertension is the highest NCD. This study aims to determine the factors associated with the incidence of hypertension based on primary health history screening of National Health Insurance (JKN) participants in the BPJS Health Semarang work area. This type of research is quantitative research with an observational analytical design. The research design is a cross-sectional study. The research used secondary data from BPJS Health regarding the results of primary health screening for JKN participants in the city of Semarang in December 2023. The total sample was 398 respondents, taken using consecutive sampling technique. Data analysis was carried out using the SPSS application, univariate and bivariate. Bivariate analysis used the chi-square statistical test with a confidence level of 95% (α=0.05). The results of the study showed that there was a relationship between age (p=0.0001), overweight/obesity (p=0.001), smoking habits (p=0.0001) and the incidence of hypertension, while there was no relationship between gender (p=1.000). with the incidence of hypertension in the BPJS Health Semarang Branch working area. It is hoped that BPJS Health will expand preventive services for JKN participants and create policies to increase the results of health history screening and reduce the incidence of hypertension.Keywords: Health history screening, hypertension, JKN participants.